Evaporation of large black holes in AdS - Rocha, J. (Journal of Physics: Conference Series, 2010)
The AdS/CFT correspondence offers a new perspective on the long-standing black hole information paradox. However, to be able to use the available gauge/gravity machinery one is forced to consider so-called ‘large’ black holes in AdS, and these objects are thermodynamically stable – they do not evaporate. We describe a simple toy model that allows large AdS black holes to decay, by coupling the emitted radiation to an external scalar field propagating in an auxiliary space. This effectively changes the properties of the boundary of AdS, making it partly absorbing. We demonstrate that the evaporation process never ceases by explicitly presenting (a) the transmission coefficient for a wave scattering from the bulk into auxiliary space and (b) the greybody factor for a black 3-brane in an AdS background. Therefore, the model provides an interesting framework to address the information paradox using AdS/CFT techniques.